2006
DOI: 10.1063/1.2166456
|View full text |Cite
|
Sign up to set email alerts
|

Small particles in homogeneous turbulence: Settling velocity enhancement by two-way coupling

Abstract: The gravitational settling of an initially random suspension of small solid particles in homogeneous turbulence is investigated numerically. The simulations are based on a pseudospectral method to solve the fluid equations combined with a Lagrangian point-particle model for the particulate phase ͑Eulerian-Lagrangian approach͒. The focus is on the enhancement of the mean particle settling velocity in a turbulent carrier fluid, as compared to the settling velocity of a single particle in quiescent fluid. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
151
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(181 citation statements)
references
References 34 publications
28
151
2
Order By: Relevance
“…strain-rate (see e.g. [2] or [5]). If particle inertia is neglected, no accumulation is observed since the particle velocity field is divergence-free for this approach.…”
Section: Results and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…strain-rate (see e.g. [2] or [5]). If particle inertia is neglected, no accumulation is observed since the particle velocity field is divergence-free for this approach.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The governing dimensionless parameters are the Reynolds number Re, the normalized Stokes settling velocity v s and the particle Stokes number St. For more details on the governing equations, see e.g. [2] and [3]. For comparison, we also present one simulation where particle inertia is neglected.…”
Section: Simulation Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical studies concerning accumulation and dispersion of heavy particles in forced plane mixing layers have been carried out in a series of works: Martin & Meiburg (1994); Raju & Meiburg (1995); Marcu & Meiburg (1996a, b); Marcu, Meiburg & Raju (1996); they all reported the formation of highly concentrated particle streaks in the region between two vortices. The behaviour of heavy particles in homogeneous isotropic turbulence has been studied experimentally by Aliseda et al (2002) and numerically by Bosse, Kleiser & Meiburg (2006) where it is shown that the settling velocity is enhanced by the turbulence and that large temporal and spatial inhomogeneities in the particle concentration fields arise; the particles concentrate preferentially in certain regions of the flow.…”
Section: Introductionmentioning
confidence: 99%